(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
The paper analyzes how headline complexes and selection rules create implicit cultural meanings in English and Uzbek online journalism. Building on Uzbek media-linguistic scholarship on the title set and psychological hooks, the study models headlines as interpretive frames that steer readers toward particular horizons of relevance. A hermeneutic approach is used to connect micro-level title choices with macro-level assumptions about authority, novelty, and public expectations in English and Uzbek media environments.